2021
DOI: 10.22270/jddt.v11i3-s.4873
|View full text |Cite
|
Sign up to set email alerts
|

Targeting β-glucan synthase for Mucormycosis “The 'black fungus” maiming Covid patients in India: computational insights

Abstract: Black fungus also known as Mucormycosis, has recently devastated some states of India. It has been declared pandemic now. Inhibitors of glucon synthesis pathways have been evaluated to curtail the Mucormycosis but still at infancy stage. Due to key role in glucon synthesis, in the present study β -glucan synthase has been regarded as a suitable target for drug design. In-silico docking and pharmacological study was designed to evaluate the effect of potent bioactive molecule 1-8 cineole present in essential oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The least binding affinity was demonstrated by (+)-curcudiol at −7.4 kcal/mol ( Table 7 ). One compound identified from the literature, 1, 8 cineole docked with exo-1,3 glucan beta synthase had shown good binding affinity [ 57 ]. However, it might not be capable of inhibiting this target.…”
Section: Resultsmentioning
confidence: 99%
“…The least binding affinity was demonstrated by (+)-curcudiol at −7.4 kcal/mol ( Table 7 ). One compound identified from the literature, 1, 8 cineole docked with exo-1,3 glucan beta synthase had shown good binding affinity [ 57 ]. However, it might not be capable of inhibiting this target.…”
Section: Resultsmentioning
confidence: 99%
“…According to recent observations, individuals who are in highly immune-compromised health circumstances following COVID-19 having diabetes or high uncontrolled sugar levels were infected with a disease produced by a "mucormycosis" (Sharma and Kaur 2021 ). The two agents currently approved by the FDA for the primary treatment of mucormycosis are amphotericin B and isavuconazole (Bhattacharya and Setia 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The two agents currently approved by the FDA for the primary treatment of mucormycosis are amphotericin B and isavuconazole (Bhattacharya and Setia 2021 ). Previous research efforts to develop antifungal agents against the Mucorales demonstrated that the inhibition of β-1,3-glucan biosynthesis by using inhibitor drugs like amphotericin/echinocandins inhibited fungal growth, thus abolished replication (Sharma and Kaur 2021 ). In the study conducted in 2014, researchers suggested that CotH3 could be an emerging therapeutic target for mucormycosis as this functions as an invasin that interacts with host cell GRP78 to mediate pathogenic host-cell interactions (Gebremariam et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to recent observations, individuals who are in highly immune-compromised health circumstances following COVID-19 having diabetes or high uncontrolled sugar levels were infected with a disease produced by a "mucormycosis" [53]. The two agents currently approved by the FDA for the primary treatment of mucormycosis are amphotericin B and isavuconazole [54].…”
Section: Discussionmentioning
confidence: 99%
“…The two agents currently approved by the FDA for the primary treatment of mucormycosis are amphotericin B and isavuconazole [54]. Previous research efforts to develop antifungal agents against the Mucorales demonstrated that the inhibition of β-1,3-glucan biosynthesis by using inhibitor drugs like amphotericin/echinocandins inhibited fungal growth, thus abolished replication [53]. In the study conducted in 2014, researchers suggested that CotH3 could be an emerging therapeutic target for mucormycosis as this functions as an invasin that interacts with host cell GRP78 to mediate pathogenic host-cell interactions [8].…”
Section: Discussionmentioning
confidence: 99%